2019
DOI: 10.1155/2019/9482350
|View full text |Cite
|
Sign up to set email alerts
|

Critical Challenges for BIM Adoption in Small and Medium‐Sized Enterprises: Evidence from China

Abstract: Building information modelling (BIM) is a set of technologies that aim to increase interorganisational and cross-disciplinary collaboration in the architecture, engineering, and construction (AEC) industries to promote productivity and the quality of design, construction, and maintenance stages of a building. Studies on BIM adoption in small and medium-sized enterprises (SMEs) have remained an under-represented area. It is necessary to understand the main challenges hindering the adoption of BIM in SMEs and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 69 publications
2
45
0
2
Order By: Relevance
“…A revolutionary emergence, BIM, offers numerous precise and practical data to the construction industry, from an improved computeraided drawing (CAD) model, to the involvement of project stockholders in a multidisciplinary working environment [54]. BIM presents considerable potential for coordination, collaboration, and integration along with improvements in information flow and data processing that reach beyond the capacity of traditional construction methods [55].…”
Section: Big Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A revolutionary emergence, BIM, offers numerous precise and practical data to the construction industry, from an improved computeraided drawing (CAD) model, to the involvement of project stockholders in a multidisciplinary working environment [54]. BIM presents considerable potential for coordination, collaboration, and integration along with improvements in information flow and data processing that reach beyond the capacity of traditional construction methods [55].…”
Section: Big Datamentioning
confidence: 99%
“…is theme optimises multidisciplinary coordination and provides a better collaborative environment. [55,100,103,104] Cost e BIM model has excellent capability for determining measures and estimations of site activities. Highly accurate estimation could be offered accordingly, thus reducing excess costs.…”
Section: Stakeholder Satisfactionmentioning
confidence: 99%
“…The absence of practical evidence capable of demonstrating an effective ROI in BIM implementation is one of the main barriers in BIM adoption for SMEs (Hosseini et al 2016). Li et al (2019) identified six critical factors and challenges for BIM adoption in SMEs, namely: limited resources, collaboration challenges, lack of BIM awareness, legal disputes and uncertainties in policies, difficulties in meeting SMEs' needs and concerns about data and information. On the other hand, Hosseini et al (2016) argued that the lack of awareness is no longer a barrier in SMEs in the Australian areas.…”
Section: Bim In Small and Medium Enterprisesmentioning
confidence: 99%
“…However, most of the existing studies are related to big and/or complex projects and focused on the design phase. Thus, several studies highlighted the lack of research for the SMEs and how SMEs are lagging behind in the adoption of BIM and in general in the implementation of new digital technologies along the lines of the industry 4.0 paradigm (Hosseini et al 2016;Lam et al 2017;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on analyses Li, Zheng, Si, and Xu (2019) proposed five strategies to mitigate challenges in BIM adoption in SMEs. These strategies, including cultivating the BIM perception of SMEs, integrated project delivery (IPD), strengthening the legal environment for BIM adoption in SMEs, and developing native software and standards and cloud-based technology, are mainly based on the view of governments, software developers, owners, and contractors who are the main stakeholders in the adoption of BIM by SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%